Sosialisasi Pengolahan Limbah Organik Menggunakan “Maggot BSF” Untuk Pakan Ayam di Dusun Dadapan, Magelang - Wangsit Aji Prakoso; Angeliu Laras Genoveva; Margaretha Intan Permatasari; Sartini Sartini; Shafa Alya Mufida; Tin Warotul Fatimah; Ignatia Esti Sumarah (Lembaga Pengembangan Kinerja Dosen, 2024)
Organic waste remains a major issue in several areas as it causes negative impacts such as environmental pollution. One of the causes is the lack of public understanding of how to process organic waste. Organic waste processing can be carried out using BSF maggot. Utilizing BSF maggot for organic waste processing is a form of sustainable benefit. BSF maggot can be used as animal feed, and its residue can be used as organic fertilizer. This study employs a qualitative method to deeply describe the sequence and results of community service activities conducted for the PKK mothers' community. The community service was conducted in the form of a socialization event aimed at providing an understanding of organic waste processing using BSF maggot and its potential as an alternative chicken feed. The activities included socialization on BSF maggot farming techniques, the role of BSF maggot in processing organic waste, the benefits that can be obtained, and the provision of BSF maggot samples for independent farming. The evaluation results show that all participants understood the BSF maggot farming techniques for processing organic waste and applying it as chicken feed in their surroundings.